Studies on the Biology, Pathogenicity and Treatment of Important Nematodes of Domestic Duck - Chandrasekharan K (Department of Parasitology, College of Veterinary and Animal Sciences, 1977)
Studies on the incidence of nematode infections in 340 domestic ducks indicated that 67.94% of birds harboured one or more species of the following nematodes viz., Amidostomum globocaudata skrjabini , capillaria contorta, capillaria , Echinuria uncinate, Epomidiostum uncinatum, Eustrongylides papilosus, Strongyloides avium and tetramers antis. The rate of infection was highest in the case of Epomidiostomum uncinatum (41.86% ) and lowest in the case of strongyloides avium (0.59%). The lifecycles of Echinuria uncinata and Tetramers anatis were worked out in detail. It was established that Tetramers anatis was distinct from Tetramers Fissispina. The complete details of the morphology of juveniles both within the intermediate and final hosts were given. The juveniles of Echinuria uncinata completed the first and second moultings on the third and fifth day respectively and the stage juveiles reached infective stage on the seventh day following infection in Daphnia pulex at a room temperature ranging from 25 to 30C0. In ducklings the juveniles underwent the third and fourth moultings on the third and seventh day respectively and the eggs of the parasite were first found in the droppings on the thirty- third day. The juveniles of Tetramers anatis completed first mopulting on the third day, the second moulting on the fifth day and the third stage encysted in fat bodies of the grasshopper, Spathosternum prasiniferum. The third stage juveniles attained infective stage on the sixth day following infection. Within the ducklings, the parasite underwent the third moulting on the third day. The fourth moulting in respect of males was seen on the nineth day and in the case of females on the tenth day. The prepatent period of the parasite was found to be 24 days. Development of the juveniles was also noticed in five other species of grasshoppers viz., Oxya nitidula, Oedaleus abruptus, Conocephalus maculatus, Ducetia Japonica and Atractomorpha crenulata. No development of Tetrameres anatis, beyound the first stage was observed inDaphnia Pulex and Daphnia Magna on experimental infection. Anaemic changes with significant reduction in weight gain and haematological values were observed in experimental infections of Tetrameres anatis, Amidostomum skrjabini and Epomidiostomum uncinatum. Histopathological changes like haemorrahage, desquamation of cells, catarrbal inflammation and necrosis were seen in experimental tetramerosis. Ulceration and atrophy were also evident in amidostomiasis and epomidiostomiasis. The anthelmintic efficacy of 9 drugs against adult worms of Tetrameres anatis, Amidostomum skrjabini and Epomidiostomum uncinatum under experimental infections were determined. The efficacies against tetramerosis, amidostomiasis and epomidiostomiasis were 79.23%,32.15% and 79.88% with Tetramisole by drochloride at 50 mg/kg body weight; 70.36%, 52.42% and 50.23% with phenothiazine at 500 mg/kg; 26.85%, 74.8% and 65.68% with Morantel tartrate at 40mg/kg; 45.70% 67.29% and 57.84% with Parbendazole at 100 mg/kg; 41,0%’63/93% and 43.13% with Thiabendazole at 200 mg/kg; 59.28%,61.06% and 52.66% with Carbontetrachloride at 2ml/kg; 35.94%, 30,12% and 13.13% with Methyridine at 200 mg/kg; 28.87% 20.17% and 11.32% with Disophenol at 10 mg/kg and 31.02%, 39.04% and 12.66% with Cashewnut shell oil at 10 g/kg body weight respeectively. The drug Rametin at 200 mg/kg was found to be fatal to ducklings. In a cross infection trial delyed development and lesser percentage of establishement of Ascaridia galli of fowl origin were observed in ducklings as compared to chicks.